Analysis of Chlorophyll-a and Sea Surface Temperature (SST) Distribution in the Waters of Karang Jeruk, Tegal Regency based on Geographic Information System (GIS) - Alamsyah, Heru Kurniawan; Irawan, Andi; Priyadi, Hermawan Gatot; Sharina, Sharina; Nugraha, Faishal Widiaputra (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
This study maps the distribution of chlorophyll-a and sea surface temperature (SST) in Karang Jeruk Waters, Tegal Regency, using Geographic Information System (GIS) with satellite data from JAXA Himawari and NOAA GFS. The mapping results on February 13, 2025, show chlorophyll-a concentrations ranging from 0.01 to 0.12 mg/m³ and SST between 25-27°C, supporting phytoplankton life and primary productivity. Water quality parameters such as salinity, temperature, pH, and clarity fall within acceptable standards, indicating that the coral reef ecosystem in this conservation area is relatively healthy. This research is expected to serve as a foundation for sustainable ecosystem management in Karang Jeruk Waters.